Concurrent Middle Cerebral Artery Occlusion and Intra-arterial Drug Infusion via Ipsilateral Common Carotid Artery Catheter in the Rat - Van Winkle, Jessica A. (2012)
Pre-clinical development of therapy for acute ischemic stroke requires robust animal models; the rodent middle cerebral artery occlusion (MCAo) model using a nylon filament inserted into the internal carotid artery is the most popular. Drug screening requires targeted delivery of test substance in a controlled manner. To address these needs, we developed a novel method for delivering substances directly into the ischemic brain during MCAo in the awake rat. An indwelling catheter is placed in the common carotid artery ipsilateral to the occlusion at the time of the surgical placement of the occluding filament. The internal and common carotid arteries are left patent to allow superfusion anterograde. The surgeries can be completed quickly to allow rapid recovery from anesthesia; tests substances can be infused at any given time for any given duration. To simulate clinical scenarios, the occluding filament can be removed minutes or hours later (reperfusion) followed by therapeutic infusions. By delivering drug intra-arterially to the target tissue, “first pass” loss in the liver is reduced and drug effects are concentrated in the ischemic zone. To validate our method, rats were infused with Evans blue dye either intra-arterially or intravenously during a 4 hour MCAo. After a 30 minute reperfusion period, the dye was extracted from each hemisphere and quantitated with a spectrophotometer. Significantly more dye was measured in the ischemic hemispheres that received the dye intra-arterially.